Analisis Faktor Penghambat Pembelajaran Membaca Permulaan pada Siswa Kelas I SDN Jati Mulya Kabupaten Tangerang - Putri Rizki Nursabila; Yeni Nuraeni; Septy Nurfadhillah (Journal on Education, 2025)
Basic reading skills are essential for success in further education. However, it has been found that many students at Jati Mulya Public Elementary School in Tangerang Regency are still unable to read fluently or recognise letters. This study aims to analyze the inhibiting factors in early reading instruction for first-grade students at SDN Jati Mulya, Tangerang Regency. The research used a descriptive qualitative approach with data collected through observation, interviews, tests, and documentation. The results reveal four main factors hindering students' early reading ability: low memory capacity, lack of reading interest, insufficient parental guidance, and low self-confidence when reading aloud. These findings are supported by observations and interviews with teachers, students, and parents, as well as reading tests based on five indicators: syllable reading, reading attitude and engagement, intonation, fluency, and letter recognition. The study concludes that both internal and external factors significantly impact students’ reading development. Collaboration between teachers, parents, and the school environment is essential to overcome these barriers and improve students’ foundational reading skills.